Menghadapi Degradasi Moral Generasi Muda Melalui Penerapan Pendidikan Islam Pada Peserta Didik - Elsa Salsabila; Muhammad Shafiq Al-Ghifari; Nursani Awal Artha Nugraha; Salis Salis; Syahidin Syahidin; Muhamad Parhan (Al-Tarbiyah : Jurnal Ilmu Pendidikan Islam, 2024)
This research discusses the moral degradation of the younger generation in Indonesia and the role of Islamic education in overcoming this problem. The phenomenon of moral degradation of the younger generation is increasingly disturbing with the increasing number of cases of tarnished morals, both in direct social interactions and via social media. The main causes of this moral degradation include promiscuity, unwise use of social media, and lack of supervision from parents. Islamic education is considered a relevant solution to face this problem. In this research, the Systematic Literature Review (SLR) method was used to collect and analyze related literature. The findings of this research show that Islamic education has an integral, progressive and functional role in overcoming the moral degradation of the younger generation. The integration of Islamic education in the school curriculum is also considered important to shape the character of students. However, there are internal and external challenges faced in implementing Islamic education, including a less comprehensive understanding of Islamic teachings, as well as the negative influence of scientific and technological progress. This research contributes to understanding the complexity of the moral degradation of the younger generation and the relevance of Islamic education as a solution in facing these challenges. Therefore, it is important for Islamic educational institutions to continue to develop effective and relevant strategies in shaping the morals of the younger generation through Islamic education.